A case–control study based on the National Health and Nutrition Examination Survey to evaluate the effects of human papilloma virus on bone health in women - Xiang Li; Guangjun Jiao; Yunzhen Chen (BMC Medicine)
Abstract Background Human papillomavirus (HPV) infection and osteoporosis (OP) are global health concerns, with higher prevalence observed in women compared to men. However, the impact of HPV infection on bone health remains uncertain. Methods This case–control study utilized data from the National Health and Nutrition Examination Survey (NHANES). Comparable datasets were created using nearest neighbor propensity score matching (PSM) at a ratio of 1:1. The association between HPV infection and bone mineral density (BMD) was analyzed using the Welch two-sample t-test. Furthermore, linear mixed models were employed for validation purposes. Restricted cubic spline (RCS) analysis and Kendall’s tau-b tests were performed to explore the effect of different types of HPV infection on BMD. Results Individuals with HPV infection (mean age 38.11 ± 11.32 years) had lower BMD in the femur and lumbar spine compared to uninfected individuals (mean age 37.92 ± 11.42 years). RCS analysis revealed that an increasing number of cooccurring HPV types in women was associated with lower BMD. Specifically, four HPV types were negatively associated with femur BMD, while 14 HPV types were negatively associated with lumbar spine BMD. Additionally, HPV types 53, 59, and 89 exhibited effects on both femur and lumbar spine BMD. Conclusions HPV infection is associated with a decrease in BMD, and co-infection with multiple types of HPV implies even lower BMD. Appropriately designed trials are needed to determine if interventions targeted at preventing HPV infection can have a protective effect on BMD.